Chronic lateral ankle pain secondary to peroneus brevis injury: a case report - Teh, Kai Hean; Singh, Gurmeet; O., Zulkiflee; Arumugam, Manohar (Ministry of Health and Universiti Brunei Darussalem, 2019)
The peroneus brevis and peroneus longus are both muscles in the lateral compartment of the leg responsible for dorsiflexion and eversion of ankle. Peroneal tendinopathy including tendinitis, rupture and dislocation has gained attention in the recent literature and is a recognised cause of lateral ankle pain. However, due to the lack of awareness of this condition, diagnosis is often missed and as a result treatment is often delayed, leading to the chronicity of the condition. This is a case report of a young lady presented with chronic left lateral ankle pain with preceding history of ankle inversion injury. Magnetic resonance imaging of her left ankle confirmed an isolated split tear of the peroneus brevis tendon. She underwent a successful peroneus tendon repair and superficial peroneal retinaculum reconstructive surgery with a good clinical outcome after 6 months of outpatient follow-up.